2022
DOI: 10.1038/s41598-021-04215-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical work accounts for most of the energetic cost in human running

Abstract: The metabolic cost of human running is not well explained, in part because the amount of work performed actively by muscles is largely unknown. Series elastic tissues such as tendon can save energy by performing work passively, but there are few direct measurements of the active versus passive contributions to work in running. There are, however, indirect biomechanical measures that can help estimate the relative contributions to overall metabolic cost. We developed a simple cost estimate for muscle work in hu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…that must be actively replaced by the muscles to maintain a constant speed (positive mechanical work) [35]. The energy dissipated by the soft tissues can be estimated by comparing different methods used to calculate the mechanical energy output of the body [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…that must be actively replaced by the muscles to maintain a constant speed (positive mechanical work) [35]. The energy dissipated by the soft tissues can be estimated by comparing different methods used to calculate the mechanical energy output of the body [38].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the mechanical energy fluctuations due to soft tissue energy dissipation (heel pad and foot arch compressions, visceral sway, cartilage and intervertebral disc compressions etc.) can also affect the mechanical work production in locomotion [3537]. During walking, the body’s soft tissues deform and dissipate a fraction of the mechanical energy (negative mechanical work) that must be actively replaced by the muscles to maintain a constant speed (positive mechanical work) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Here, we chose the metabolic work as proxy for overall metabolic cost of walking. The validity of this proxy can be justified by the fact that in both isolated leg swinging ( Doke, Donelan & Kuo, 2005 ) and in locomotion ( Riddick & Kuo, 2022 ), the joint mechanical power and metabolic power are monotonically related, suggesting that lower metabolic work can be a proxy for lower metabolic cost and higher energy efficiency. Still, we overestimated the metabolic cost at the ankle and hip joints (dimensionless MCOT for humans is 0.23 and for our optimal gait is 0.38 at the same human preferred speed), due to the fact that humans generate burst-like hip torques rather than spring-like hip torques, and due to storage and release of elastic energy at tendons.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we chose the metabolic work as proxy for overall metabolic cost of walking. The validity of this proxy can be justified by the fact that in both isolated leg swinging (Doke et al, 2005) and in locomotion (Riddick & Kuo, 2022), the joint mechanical power and metabolic power are monotonically related, suggesting that lower metabolic work can be a proxy for lower metabolic cost and higher energy efficiency. Still, we overestimated the metabolic cost at the ankle and hip joints (dimensionless MCOT for humans is 0.23 and for our optimal gait is 0.38 at the same human preferred speed), due to the fact that humans generate burst-like hip torques rather than spring-like hip torques, and due to storage and release of elastic energy at tendons.…”
Section: Discussionmentioning
confidence: 99%